Political Law of Electronic System Implementation in Indonesia - A.E. Isfihani; Izomiddin; Antasari, Rr. Rina; Muhammad Sadi Is (Universitas Islam Negeri Raden Fatah Palembang, 2024)
In a rapidly evolving digital landscape, understanding the legal and political dimensions of electronic system regulation is critical to facilitating responsible, transparent, and effective governance. This research aims to explore the legal politics of implementing electronic systems in Indonesia. This regulation is crucial in the context of modern governance, as it deals with the operation and management of electronic systems, a significant aspect in contemporary society. This study examines legal aspects, assessing the compliance of Regulation No. 05/2020 with existing legislation and international standards, while also exploring its practical implications. These regulations address issues such as data protection, cybersecurity, and the role of electronic systems in public administration, requiring a careful analysis of their legal power and effectiveness. Additionally, the study investigates the political dimension of regulation, considering its implications for governance and democracy. It examines the potential impact of these regulations on citizens' rights, government control, and transparency in the digital age, focusing on how these regulations affect political power dynamics and civic engagement. Therefore, the study concludes by highlighting the importance of Regulation No. 05/2020 and emphasizing the need for a balanced approach that ensures legal compliance and political integrity, while also encouraging the growth and development of electronic systems within legal and political frameworks.